DISPARITAS PEMIDANAAN DALAM TINDAK PIDANA ASUSILA TERHADAP ANAK DIBAWAH UMUR: STUDI KASUS PUTUSAN NOMOR 21/PID.SUS/2019/PN PDP DAN 172/PID.SUS/2020/PN SBS - Gustiawan, Putra Chusnul; Prasetyo, Bayu; Elviandri, Elviandri (Gapenas Publisher, 2025)
Indonesia, as a state based on law as stipulated in Article 1 paragraph (3) of the 1945 Constitution, is obliged to guarantee the protection of human rights, including the rights of children as a vulnerable group. Child protection is reinforced through Article 28B of the 1945 Constitution and Law No. 35 of 2014 in conjunction with Law No. 17 of 2016, which explicitly prohibit all forms of sexual violence against children. Philosophically, child protection reflects respect for human dignity; juridically, it is a constitutional mandate and statutory obligation; while sociologically, it is necessary to prevent the destruction of future generations caused by sexual violence. The urgency of this research arises from the increasing number of sexual violence cases against children and the presence of sentencing disparities, as reflected in Decision No. 21/Pid.Sus/2019/PN Pdp and Decision No. 172/Pid.Sus/2020/PN Sbs. This study aims to analyze judicial considerations in both decisions and identify their implications for victims, perpetrators, and society. The research applies a normative juridical method with statutory and case approaches, supported by primary and secondary legal materials analyzed descriptively and analytically. The findings show that judges based their rulings on Article 82 paragraph (1) of the Child Protection Law, taking into account trial evidence, psychological impacts on victims, and violated social values. However, disparities emerged: six years’ imprisonment with an IDR 800 million fine in the Pdp case, and seven years’ imprisonment with only an IDR 60 million fine in the Sbs case. Such inconsistencies undermine legal certainty and judicial legitimacy. In conclusion, although sentencing has reflected criminal accountability, a balance between retributive and restorative aspects is lacking. Clear sentencing guidelines and stronger protection and recovery measures for child victims are therefore recommended to realize substantive justice.